Thermo-Mechanical Properties of Polypropylene Blends with Esterified Lignin - Rogerio Ramos de Sousa Junior; Guilherme Elias Saltarelli Garcia; Manuel Patricio da Silva Bisneto; Laura Gouveia de Freitas; Tamiris Basan Hubmann; Túlio Morás Coutinho; Demetrio Jackson dos Santos (AppliedChem)
Lignin, a renewable and widely available biopolymer, has been explored as an additive in polyolefins to develop high value-added materials. However, its low compatibility with polymers like polypropylene (PP) often causes poor particle dispersion and compromised mechanical properties. Esterification has proven effective in enhancing lignin-polyolefin interactions. This study evaluated the incorporation of kraft lignin (KL) and maleic anhydride-modified kraft lignin (MAKL) into PP, focusing on lignin dispersion and the blends’ thermal, mechanical, and viscoelastic properties. Thermal analyses showed that MAKL reduced PP crystallinity, indicating improved compatibility, supported by micrographs showing more uniform particle dispersion. Mechanically, low MAKL concentrations maintained yield strength similar to neat PP, while 5 wt% MAKL increased impact strength by up to 148%. This improvement was attributed to enhanced interfacial interaction, reduced crystallinity, and better energy dissipation. The findings demonstrate that esterification of lignin with maleic anhydride effectively overcomes compatibility limitations with PP, leading to significant gains in mechanical and viscoelastic properties. This work advances lignin’s sustainable use in polymer blends, emphasizing its potential as a renewable alternative in material development.